FAKTOR YANG MEMPENGARUHI PURCHASE DECISION PADA KONSUMEN TOKOPEDIA DI DKI JAKARTA - Nuzully, Muhammad; Indriyanti, Irma Satya (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
With advances in technology, there has been a shift in people's behavior, which previously shopped at traditional markets, now has shifted to shopping online through e-commerce. Therefore companies need to build a strong brand in order to show the value of the product or service they offer. This study aims to determine the effect of brand awareness, perceived quality, brand association and brand loyalty on purchase decisions among Tokopedia consumers in DKI Jakarta. In this study using primary data obtained from distributing questionnaires using five Likert scale as a variable measurement. This research uses non-probability sampling with purposive sampling technique. The researcher used the multiple linear regression analysis method to find out the causal relationship between variables. This study collected 124 respondents using the Tokopedia application in DKI Jakarta and the distribution was carried out online via the Google form. The results of this study state that there is an influence of brand association and brand loyalty on purchase decisions, whereas there is no influence of brand awareness and perceived quality on purchase decisions.